THE IMPLEMENTATION OF TEACHING GRAMMAR SIMPLE PAST TENSE THROUGH SONGS - Ramadhanti, Sarah Yusningsih; Haryudin, Acep (PROJECT (Professional Journal of English Education), 2021)
Songs become an interesting media which can be implemented by English teacher to teach various language skills, one of which is teaching grammar. Songs contains many series of words arranged as lyrics and also have various grammatical structure. This paper was aimed to describe the implementation of teaching grammar, especially simple past tense through English songs. This technique was implemented at eleventh grade students of Islamic High School in Padalarang. The researchers have done a total of three meetings and presented 2 songs in the classroom. Qualitative method has been used as a research method in this study. Qualitative data were obtained by conducting observation at each meeting to find out classroom activity, and held a test for students in the last meeting to find out the extent to which students’ understanding after they they got the teaching-learning activities. The result of this research reveals that the implementation of teaching grammar simple past tense through songs has been implemented successfully. Keywords: Teaching Grammar, Simple Past Tense, Songs